The role of hypervolemic and stroke volume in the heart rate and oxygen relationship following intense training - Richardson, R. S.; Verestraete, D.; Hochstein, A.; Schultz, W.; Johnson, S. C.; Luetkemeier, M. J.; Stray-Gundersen, J. (Medicine & Science in Sports & Exercise, 1993)
The effect of acute exercise training on HR, oxygen consumption (VO2), cardiac output (CO), stroke volume (SV), plasma volume (PV), and running speed was studied in 14 male competitive runners. Two days of intense training (90-95% VO2max) followed baseline determinations. HRmax was significantly reduced following the intense training (183 to 179 bpm). Both CO and VO2 were unaffected. PV increased by an average 6%. SV increased by an average of 4%. CO was maintained by SV. Implication: The relationship between HR and VO2 is affected by training intensity. These changes in trained athletes may be the result of a secondary PV expansion produced by intense effort which raises SV and decreases HR.